The Compliance of Regional Autonomy with State Administrative Court Decisions - Baranyanan, Soeleman Djaiz; Firmandayu, Nilam; Danendra, Ravi (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2024)
Divergent mechanisms governed by several laws in force in Indonesia continue to impede the implementation of decisions rendered by state administrative courts. As a result, issues about the nature of government autonomy, legal consciousness, leadership structures, and political determination arise in the context of regional autonomy. The employed research methodology is normative juridical research, which analyzes articles in the law on state administrative courts about the execution of state administrative court institutions' decisions to identify and formulate legal arguments. This study demonstrates discrepancies in how decisions are executed by state administrative tribunals in Indonesia and several challenges associated with their practical implementation. In order to address these challenges, four conceptual frameworks of executive authority have been developed to establish a mechanism for implementing administrative court rulings in a globalized environment. The evolution model of legal instruments for implementing decisions of state administrative courts, the defense model for various types of implementation such decisions, the law enforcement model for executing state administrative courts, and the execution model as a question vacate.